A few reflections about the career of magister militum Flavius Plinta and his influences on the court of Theodosius II - Pigoński, Łukasz (Balcanica Posnaniensia. Acta et studia, 2021)
The subject of my study is an attempt to reconstruct the career and military activities of Magister Militum Flavius Plinta, described in the Sozemon’s Church History writings. The writings are considered to be on of the sparce sources of information about this politician and commander of the Greek origin, living in the 5th C.E. The source indicates that Flavius Plinta was an influential person on the Byzantine court. Essential to his influential position were the relations with the Goths, whom the Empire settled in Thracia to control the Huns problem. Moreover, F. Plinta was the first of the powerful Magistri Militum in the Eastern Roman Empire, who used their status in the military system to gain political influence.